Mosque Transformation for Community Economic Empowerment: Integrating Islamic Social Finance, Digitalization, and Pentahelix Collaboration - Mulauddin, Aforisma; Waluya , Atep Hendang; Reza Prima Matondang, Muhammad (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2025)
Mosques have a long-standing history as the center of Islamic civilization, including in economic activities. However, their strategic role has been reduced to mere places of ritual worship. This article aims to formulate an integrated conceptual model of economic empowerment based on mosques, incorporating Islamic social finance, digital transformation, and multi-stakeholder collaboration (pentahelix). The study employs a qualitative library research method with a conceptual analysis approach. Findings reveal that mosques hold great potential as centers of economic empowerment through the optimization of ZISWAF instruments, digital technologies such as fintech and mosque management applications, and synergy among academia, business, government, community, and media. Case studies from Jogokariyan Mosque, Al-Falah Mosque Seoul, and Bintaro Jaya Grand Mosque demonstrate the successful implementation of such models in various contexts. The article proposes financial, social, and technological evaluation indicators to assess model effectiveness. Consequently, mosques can emerge as adaptive beacons of economic empowerment in the digital era.